Drosophila rae1 is required for male meiosis and spermatogenesis. - Volpi, S.; Bongiorni, S.; Fabbretti, F.; Wakimoto, B.T.; Prantera, G. (Journal of Cell Science, 2013)
Previous studies of RAE1, a conserved WD40 protein, in Schizosaccharomyces pombe and mouse revealed a role in mRNA export and cell cycle progression in mitotic cells. Studies of RAE1 in Drosophila showed that the protein localizes to the nuclear envelope and is required for progression through the G1 phase of the cell cycle but not RNA export in tissue culture cells. Drosophila RAE1 also plays an essential developmental role, as it is required for viability and synaptic growth regulation as a component of an E3 ubiquitin ligase complex. Here we describe characterization of a new Drosophila rae1 mutant that is viable but results in male sterility. The mutant showed striking defects in primary spermatocyte nuclear integrity, meiotic chromosome condensation, segregation, and spindle morphology. These defects led to a failure to complete meiosis but allowed several aspects of spermatid differentiation to proceed, including axoneme formation and elongation. A GFP-RAE1 fusion protein that rescued most of the cytological defects showed a dynamic localization to the nuclear envelope, chromatin and other structures depending on the stage of spermatogenesis. A role for RAE1 in male meiosis, as well as mitotic cells, was also indicated by the defects induced by expression of rae1-RNAi. These studies in Drosophila provide the first evidence for an essential meiotic role of RAE1, and thus define RAE1 as a protein required for both meiotic and mitotic cell cycles.